O serviço social na Previdência social no Brasil: marchas, contramarchas na particularidade da intervenção profissional no INSS. - SOUZA , Ana Patrícia dos Anjos (2021)
Study on Social Work in Social Security in Brazil, based on socioeconomic and political determinations at different times, with highlighting advances and achievements as well as setbacks and challenges, privileging the particularity of professional intervention at the National Social Security Institute (INSS). It demarcates the historical process of the profession in Social Security as a professional practice inserted in contradictory social relations, mediating and being mediated by antagonistic interests posed by governmental intervention strategies in the relationship between capital and work in different care to the demands of both employers and workers. The main historical milestones of the trajectory of Social Security are highlighted as Social Security and, later, as Social Security inserted in the Brazilian social protection system, pointing out contradictions and singularities. It develops an analysis of the professional intervention in the INSS based on the Basic Action Plans of 1972 and 1978, of the Methodological Theoretical Matrix and Technical Manual of Social Service in Social Security. Highlights strategies of the Brazilian State guided by the neoliberal dictates under the global hegemony of financial capital, from the reform of the State apparatus and the reforms of Social Security that weaken Public Security, as a public policy of Social Security with significant implications for working conditions and in the professional intervention of Social Workers in the INSS. In this way, there are the challenges posed to the Social Service of Social Security in defense of its socio-occupational space as well as the professional intervention guided by the ethical-political project in the face of the threat of extinction of the profession as a relevant social security service for the achievement users' rights in the scope of Public Welfare.